Profit efficiency among peri-urban dairy farms in Odisha: an application of the stochastic frontier function - Kamlesh Kumar Acharya; Ravinder Malhotra; R Sendhil; Binita Kumari (Agricultural Economics Research Review, 2023)
This study examines the profit efficiency of peri-urban dairy farms in Odisha. Inefficiencies are found, and the profit efficiency ranges from 2% to 92%; the mean is 54%. The mean profit efficiency is 76% for large farms, the highest, 64% for medium-size farms, and 60% for small farms. Concentrate price and labour wage rates affect profits significantly. Profit inefficiency is impacted positively and significantly by herd size and negatively and significantly by herd composition; decreasing the herd size and increasing the number of crossbred cows would enhance profit efficiency. Improving education and dairy farm experience would enhance the profit efficiency.